Review Essay: A Queer Century: 1869-1969 - Duranseaud, Noah (Papers of the Bibliographical Society of Canada / Cahiers de la Société bibliographique du Canada, 2019)
This note focuses on the exhibition A Queer Century 1869-1969, which was on display from June 1st 2019 to September 11th, 2019 at the University of British Columbia’s Rare Books and Special Collections. The note describes the details of the exhibition, going through cases, notable and rare literary works, and discussions with the co-curators of the exhibition, Dr. Kyle Frackman and Dr. Gregory Mackie.